Stereo Perfect Metamaterial Absorber Based on Standing Gear-Shaped Resonant Structure With Wide-Incident-Angle Stability - Deng, Guangsheng; Lv, Kun; Sun, Hanxiao; Yin, Zhiping; Yang, Jun (Frontiers in Physics, 2020)
In this work, a single-band metamaterial absorber (MA) based on a three dimensional (3D) resonant structure is presented. The unit cell is composed of a standing gear-shaped resonator, which is embedded in the dielectric substrate. The proposed 3D MA is ultrathin with a total thickness of 2.3 mm, corresponding 0.077λ0 at its center frequency. The simulation results demonstrate a high absorption peak at 10.1 GHz with absorptivity of 99.9%. The proposed 3D MA is insensitive to the polarization of the incident wave due to its rotationally symmetric structure. Moreover, the proposed 3D MA exhibits a wide-incident-angle stability, as absorptivity of more than 85% can be achieved for both TE and TM incidences with incident angle up to 60°. Most importantly, multiband electromagnetic wave absorption of the stereo MA can be enabled by adjusting the structural parameters of the standing gear. The proposed structure is compatible with 3D printing technology and has potential applications in electromagnetic shielding.